LEGAL FOUNDATIONS OF INHERITANCE AND HEIRSHIP - Azirbaev Salamat Kuanishbaevich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article provides a detailed analysis of inheritance and the fundamental principles governing it. The legal basis of inheritance is examined in accordance with inheritance law, including key concepts such as wills and testamentary succession.